2020
DOI: 10.1016/j.sjbs.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring of the biomass and production of lipids by Nitzschia palea for biodiesel production

Abstract: Pennate diatom Nitzschia palea can be cultured in outdoor vertical-bed photobioreactors to produce biodiesel. To assess the production of biomass and lipids, non-axenic cultures of Nitzschia palea were grown outdoors, and the growth of these cultures was measured biweekly. During the annual cycle of algal culture, the culture temperature ranged from 17.3 °C to 33.5 °C, the dry weight biomass ranged from 0.11 g l −1 to 0.25 g l −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The relevance of OD and Fo was demonstrated during the exponential phase only (days 4 -17), as they both positively correlated with cell density in a linear regression model (R 2 > 0.89, n = 45). Preliminary results on the fatty acid (FA) composition indicated that the major FAs produced by N. palea were palmitic acid (18 -41 %) and palmitoleic acid (12 -25 %), in accordance with a previous study (Touliabah et al, 2020). As for the ω-3 FAs, DHA was poorly produced (≤ 3%), while EPA constituted a major FA for two of the strains (21% and 13%).…”
Section: Growth and Fatty Acid Production Of Three Native Canarian St...supporting
confidence: 87%
“…The relevance of OD and Fo was demonstrated during the exponential phase only (days 4 -17), as they both positively correlated with cell density in a linear regression model (R 2 > 0.89, n = 45). Preliminary results on the fatty acid (FA) composition indicated that the major FAs produced by N. palea were palmitic acid (18 -41 %) and palmitoleic acid (12 -25 %), in accordance with a previous study (Touliabah et al, 2020). As for the ω-3 FAs, DHA was poorly produced (≤ 3%), while EPA constituted a major FA for two of the strains (21% and 13%).…”
Section: Growth and Fatty Acid Production Of Three Native Canarian St...supporting
confidence: 87%
“…The relatively high percentage of palmitoleic acid as well as palmitic acid in the S. obliquus under the study conditions indicates its suitability as a feedstock for the production of biodiesel. A similar conclusion was stated by Touliabah et al [53]; according to their lipid analysis, more than 70% of the lipids were composed of C16:0 and C16:1 palmitic and palmitoleic acids. There was a high percentage of low-density fatty acids, which are thought to be the best fatty acids for producing biodiesel with a very high technical grade [23].…”
Section: Biodiesel Production From S Obliquus Under Optimized Conditionssupporting
confidence: 86%
“…Many previous studies have examined the microalgal lipids as a sustainable and environmentally friendly source for biodiesel ( Griffiths and Harrison, 2009 , Schnurr and Allen, 2015 , Almarashi et al, 2020 ). However, to be economically feasible, microalgal cultivation must have high productivity of biomass and efficient production of lipids ( Go et al, 2012 , Touliabah et al, 2020 ). In order to enhance the productivity of biomass and lipids, researchers have applied different abiotic stresses to the microalgal cells (e.g., nutrient deprivation, low pH, high salinity, high light level, high temperature, and UV radiation) to stimulate the synthesis and accumulation of lipids ( Gomaa, 2018 , El-Sheekh et al, 2019 , Abomohra et al, 2019 , Chen et al, 2017 , Paliwal et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%